How climate change comes to matter : the communal life of facts - Callison, Candis, 1971- (Experimental futures., 2014)
A rich ethnographic account describing the processes by which climate change comes to matter collectively and individually, and how vernacular explanations of climate change reflect diverse ways of knowing and caring about the world.